The Effects of Cognitive Reappraisal and Expressive Suppression on Memory of Emotional Pictures - Wang, Yan Mei; Chen, Jie; Han, Ben Yue (Frontiers in Psychology, 2017)
In the field of emotion research, the influence of emotion regulation strategies on memory with emotional materials has been widely concerneddiscussed in recent years. However, existing studies have focused exclusively on regulating negative emotion but not positive emotion. Therefore, iIn present study, we investigated the influence of emotion regulation strategies for positive emotion on memory. this study, 120 college students were selected as participants. Emotional pictures (positive pictures, negative and neutral pictures) were selected from CAPS Chinese Affective Picture System (CAPS) as experimental materials. We employed a mixed experimental design, 4 (emotion regulation strategies: cognitive up-regulation, cognitive down-regulation, expressive suppression, passive viewing) × 3 (Emotionalemotional pictures: positive, neutral, negative).) experimental design. We investigated the influences of different emotion regulation strategies on the performance of memory of three kinds of emotional picturesperformance , using free recall task and recognition task. tasks with pictures varying in emotional content. The results showed that the performance of recognition memory and the performance of free recall memory performance of the cognitive appraisal groups (up-regulation and down-regulation) were both better than that of the passive viewing group for all emotional pictures. No significant differences were reported forin the two kinds of memory scores between the expressive suppression group and passive view group.viewing groups. The results also showed that the memory performance with the emotional pictures differed according to the form of memory test. For the recognition test, participants performed better with positive images than with neutral images. Free recall scores with negative images were higher than those with neutral images. These results suggest that both cognitive reappraisal regulation strategies (up-regulation and down-regulation) promoted explicit memories of the emotional content of stimuli, and the form of memory test influenced performance with emotional pictures.